Rekonstruksi Media Pembelajaran Mobile Learning Berbasis Web Quizizz pada Mata Pelajaran Fiqih Kelas XI Madrasah Aliyah - Lilawati, Emi; Cahyono, Muhamad Nur; Chotimah, Chusnul (YASIN, 2025)
This study aims to develop a web-based mobile learning media quizizz, determine the feasibility of the media and to improve students' understanding of the subject of fiqh for class XI MA. This media was chosen to answer the problem of students' lack of understanding of the subject of fiqh due to boring learning methods, so that students play more on their cellphones during learning. This study uses the RnD or Research and Development method, which is a method for making certain products and testing how effective the product is. the model used is the ADDIE model which consists of Analysis, Design, Development, Implementation, and Evaluation. The results of this study indicate that the media developed is feasible to be tested with a score of 89% for material experts and 85% for media experts. This media is also able to improve students' understanding with a percentage increase in value of 54%. So it can be concluded that the media developed is feasible to be used in learning and is able to improve students' understanding. This media is also expected to be able to answer problems in education today, by presenting interesting and innovative learning media.